Lack of association between oral bisphosphonates and osteonecrosis using jaw surgery as a surrogate marker. - Pazianas, M; Blumentals, W; Miller, P (2008)
UNLABELLED: Using jaw surgery as a surrogate marker for osteonecrosis of the jaw, this exploratory study did not find that the risk of jaw surgery was significantly increased with the use of oral bisphosphonates in postmenopausal women. INTRODUCTION: The objective of this analysis was to explore the potential association between jaw surgery (as a surrogate marker for osteonecrosis of the jaw) and the use of oral bisphosphonates in postmenopausal women. METHODS: A claims database was used to identify female patients > or = 45 years of age with jaw surgery claims from January 1, 2002 to December 31, 2005. Four controls (patients with no claims for jaw surgery) were matched to each jaw surgery case. Additional patient data collected included oral bisphosphonate prescriptions (including alendronate, risedronate, or ibandronate) and comorbid conditions. RESULTS: A total of 697 jaw surgery cases and 2,808 controls were identified. Of those jaw surgery cases, 96 (13.8%) received at least one prescription for an oral bisphosphonate. After adjustment for confounding variables, receiving at least one oral bisphosphonate prescription was not shown to significantly increase the risk of jaw surgery (odds ratio(adjusted) = 0.91; 95% confidence interval = 0.70-1.19). When bisphosphonate use was stratified by duration on therapy, no significant increases in the risk of jaw surgery were observed in any group. CONCLUSIONS: This exploratory analysis did not find a significant association between oral bisphosphonate use and increased risk of jaw surgery, a surrogate marker for osteonecrosis of the jaw.